Ten-Year Review of Candidemia in a Canadian Tertiary Care Centre: Predominance of Non-albicans Candida Species - Ghada N Al-Rawahi; Diane L Roscoe (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To review the epidemiology and associated risk factors for candidemia at a tertiary care centre, in view of recent reports on the changing epidemiology of bloodstream infection due to Candida species.